Comorbidity Burden in Adults With Autism Spectrum Disorders and Intellectual Disabilities—A Report From the EFAAR (Frailty Assessment in Ageing Adults With Autism Spectrum and Intellectual Disabilities) Study - Miot, Stéphanie; Akbaraly, Tasnime; Michelon, Cecile; Couderc, Sylvie; Crepiat, Sophie; Loubersac, Julie; Picot, Marie-Christine; Pernon, Éric; Gonnier, Véronique; Jeandel, Claude; Blain, Hubert; Baghdadli, Amaria (Frontiers in Psychiatry, 2019)
Background: Autism spectrum disorder (ASD) is an early-onset and lifelong neurodevelopmental condition frequently associated with intellectual disability (ID). Although emerging studies suggest that ASD is associated with premature ageing and various medical comorbidities, as described for ID, data are scarce. Objectives: To determine the comorbidity burden and its association with distinct clinical presentation in terms of ASD severity, adaptive skills, level of autonomy, and drug exposure in a well-phenotyped sample of individuals with ASD-ID – the EFAAR cohort. Methods: A total of 63 adults with ASD-ID, with a mean age of 42.9±15.1 years, were recruited from 2015 to 2017 from nine specialized institutions. They underwent detailed clinical examinations, including screening for comorbidities, ASD severity (CARS), adaptive functioning (VABS-II), autonomy (ADL), and drug use (polypharmacy and the Drug Burden Index (DBI)). The comorbidity burden was evaluated using the Cumulative Illness Rating Scale (CIRS-G) and its sub-scores (the severity index (CIRS-SI) and severe comorbidity (CIRS-SC)). Results: We found a large range of comorbidities, including gastro-intestinal disorders and mental and neurological diseases. Overall, 25% of our ASD-ID sample had chronic kidney disease with the associated increased cardiovascular risk factors. The comorbidity burden was high (mean CIRS-G total score of 10.6 ± 4.8), comparable to that observed among patients older than those in our population hospitalized in geriatrics departments. Furthermore, the comorbidity burden positively correlated with age, decreased autonomy, and polypharmacy. Conclusion: The severity of the comorbidity burden associated with premature ageing in adults with ASD and ID highlight their crucial need of personalized medical care.